2009
DOI: 10.1200/jco.2009.27.15_suppl.2059
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum urokinase plasminogen activator (uPA) to progression of recurrent malignant glioma during bevacizumab treatment: A marker of invasive phenotype and a candidate to monitor therapy

Abstract: 2059 Background: Identification of circulating markers that predict tumor response or reflect progression is of crucial importance when using antiangiogenic agents. However, to date, no such parameters have been identified particularly for bevacizumab, for which, recently, increasing data have supported a role in patient with recurrent malignant glioma. Methods: Serial serum levels of VEGF, VEGFR2, FGF, SDFα, urokinase plasminogen activator (uPA), plasminogen activator inhibitor type I (PAI-1), and metallopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Proposed research methods for evaluating response to bevacizumab include assaying for angiogenic factors (eg, serum or urinary VEGF, basic fibroblast growth factor, matrix metalloproteinase, or urokinase plasminogen activator) or ex vivo markers (eg, circulating endothelial cells); biopsy analysis (to determine tumor density and drug–target interactions); and radiographic assessment (calculating fuoro-L-thymidine-PET response, changes in the apparent diffusion coefficient, or the ratio of fluid-attenuated inversion-recovery [FLAIR] volume to contrast-enhancing tumor volume). 67,6973…”
Section: Practical Issues Regarding Bevacizumab Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed research methods for evaluating response to bevacizumab include assaying for angiogenic factors (eg, serum or urinary VEGF, basic fibroblast growth factor, matrix metalloproteinase, or urokinase plasminogen activator) or ex vivo markers (eg, circulating endothelial cells); biopsy analysis (to determine tumor density and drug–target interactions); and radiographic assessment (calculating fuoro-L-thymidine-PET response, changes in the apparent diffusion coefficient, or the ratio of fluid-attenuated inversion-recovery [FLAIR] volume to contrast-enhancing tumor volume). 67,6973…”
Section: Practical Issues Regarding Bevacizumab Administrationmentioning
confidence: 99%
“…Proposed research methods for evaluating response to bevacizumab include assaying for angiogenic factors (eg, serum or urinary VEGF, basic fibroblast growth factor, matrix metalloproteinase, or urokinase plasminogen activator) or ex vivo markers (eg, circulating endothelial cells); biopsy analysis (to determine tumor density and drugtarget interactions); and radiographic assessment (calculating fluoro-L-thymidine-PET response, changes in the apparent diffusion coefficient, or the ratio of fluid-attenuated inversion-recovery [FLAIR] volume to contrast-enhancing tumor volume). 67,[69][70][71][72][73] As a secondary benefit, bevacizumab has been shown to decrease both tumoral and peritumoral edema in patients with GBM, thereby reducing the requirement for chronic corticosteroid use. Several studies have reported that corticosteroid reductions were feasible in 33% to 59% of patients with recurrent GBM following bevacizumab treatment, 32,34,36,46,49,74 and 2 trials have reported average corticosteroid dose reductions of 72% and 59%, 36,74 respectively.…”
Section: Practical Issues Regarding Bevacizumab Administrationmentioning
confidence: 99%
“…Another study has evaluated circulating serum levels of markers that may predict tumor response or progression during treatment with bevacizumab and irinotecan. 120 In a series of 32 patients with recurrent malignant gliomas, serial serum levels of VEGF, VEGFR-2, FGF, urokinase plasminogen activator (uPA), plasminogen activator inhibitor type I (PAI-1), and MMP-9 were drawn pre-treatment and at four week intervals until progression. None of the pre-treatment serum levels significantly affected PFS or overall survival.…”
Section: Discussionmentioning
confidence: 99%